2015
DOI: 10.1038/ijo.2015.253
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicinoids: a spicy solution to the management of obesity?

Abstract: Capsaicin is the molecule that is responsible for the pungency of hot peppers. It stimulates the sympathoadrenal system that mediates the thermogenic and anorexigenic effects of capsaicinoids. Capsaicinoids have been found to accentuate the impact of caloric restriction on body weight loss. Some studies have also shown that capsinoids, the non-pungent analogs of capsaicinoids, increase energy expenditure. Capsaicin supplementation attenuates or even prevents the increase in hunger and decrease in fullness as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 65 publications
1
53
0
2
Order By: Relevance
“…Spiciness (trigeminal heat) as a weight management strategy (Berridge & Fentress, ; Carstens et al, ; Delwiche, ; Dessirier, O'Mahony, & Carstens, ; Dessirier, Simons, Sudo, Sudo, & Carstens, ; Golzarand, Toolabi, & Aghasi, ; Green, ; Janssens, Hursel, Martens, & Westerterp‐Plantenga, ; Janssens, Hursel, & Westerterp‐Plantenga, ; Kostyra, Baryłko‐Pikielna, & Dąbrowska, ; Lawless & Stevens, ; Ludy & Mattes, ; Prakash & Srinivasan, ; Rozin, ; Spence, , ; Spence & Wang, ; Tremblay, Arguin, & Panahi, ; Urbina et al, ; Whiting, Derbyshire, & Tiwari, , ; Yoshioka et al, )…”
Section: A Chemesthetic Culinary Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Spiciness (trigeminal heat) as a weight management strategy (Berridge & Fentress, ; Carstens et al, ; Delwiche, ; Dessirier, O'Mahony, & Carstens, ; Dessirier, Simons, Sudo, Sudo, & Carstens, ; Golzarand, Toolabi, & Aghasi, ; Green, ; Janssens, Hursel, Martens, & Westerterp‐Plantenga, ; Janssens, Hursel, & Westerterp‐Plantenga, ; Kostyra, Baryłko‐Pikielna, & Dąbrowska, ; Lawless & Stevens, ; Ludy & Mattes, ; Prakash & Srinivasan, ; Rozin, ; Spence, , ; Spence & Wang, ; Tremblay, Arguin, & Panahi, ; Urbina et al, ; Whiting, Derbyshire, & Tiwari, , ; Yoshioka et al, )…”
Section: A Chemesthetic Culinary Strategymentioning
confidence: 99%
“…Although the current literature on the benefits of incorporating chili peppers into a healthy diet is limited, Figure 1 depicts the ways in which trigeminal stimuli have been shown or suggested to modify food intake and satisfaction, and these topics will be discussed throughout this paper. In addition to maintaining consumer satisfaction with less food and adding a dimension to flavor complexity (the third chemical sense), trigeminal stimuli have the potential to increase the perception of other tastes and odors, reduce the eating rate, suppress the appetite, increase micronutrient absorption, and possibly increase the metabolism, all factors that could lead to weight loss (Berridge & Fentress, 1985;Carstens et al, 2002;Delwiche, 2004;Dessirier et al, 2000Dessirier et al, , 2001Golzarand et al, 2018;Green, 1996a;Janssens et al, 2013Janssens et al, , 2014Kostyra et al, 2010;Lawless & Stevens, 1984;Ludy & Mattes, 2011;Prakash & Srinivasan, 2013;Rozin, 1990;Spence, 2018aSpence, , 2018bSpence & Wang, 2018;Tremblay et al, 2016;Urbina et al, 2017;Whiting et al, 2012Whiting et al, , 2014Yoshioka et al, 2004).…”
Section: A Chemesthetic Culinary Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it appears that capsaicinoid ingestion may also alter food choice in a macronutrient-specific way, by promoting carbohydrate consumption over fat consumption [5,53]. Despite repeated observations that capsaicin consumption reduces ad libitum intake in both rodents and humans [67], one large population study including over 400,000 Chinese adults showed that the integration of spicy foods was associated with higher anthropometric measurements, suggesting the addition of spicy food alone may be insufficient to prevent obesity [68].…”
Section: Capsaicin and Regulation Of Hunger Satiety And Energy Expementioning
confidence: 99%
“…Another potential benefit of capsaicinoid consumption for metabolic disease is heightened resting energy expenditure (especially if coupled with reduced energy intake). Several recent reviews have reported capsaicin's potential for stimulating weight management may be of modest proportion (roughly 50 kcal/day through enhanced energy expenditure), with beneficial effects of capsaicin on energy expenditure occurring in 13 of the 15 critically reviewed experiments [53,68]. Moreover, although capsaicin consumption may not consistently cause weight loss, the authors speculate that the improved lipid oxidation and molecular effects of capsaicin may lead to multiple other health benefits [53].…”
Section: Capsaicin and Regulation Of Hunger Satiety And Energy Expementioning
confidence: 99%